The Effect of Plyometrics Training Methods and Height on Leg Power, Volleyball Smash Ability on Christian University Athlete Club Artha Wacana Kupang - Maximus Nggana; Nasuka Nasuka; Andry Akhiruyanto (Journal of Physical Education and Sports, 2022)
The purpose of this study was to determine and analyze: 1) the difference in the effect of depth jump and jump to box training on volleyball smash ability in athletes of Club Universitas Kristen Artha Wacana Kupang. 2) the difference in the effect between above-average and below-average height and low leg power in the athlete club of Universitas Kristen Artha Wacana Kupang. 3) the interaction between training methods and height on volleyball smash ability in athletes of Club Universitas Kristen Artha Wacana Kupang. This study used an experimental method with a design with a factorial 2x2. Data analysis technique using Analysis of Variance (Anova) At significant level (a) 0.05. The independent variable in this study is the depth jump and jump to box training methods. Height above average and below average as attribute variables and dependent variables are volleyball smash ability at the Artha Wacana Christian University Kupang club. The results of this study (1) There is a significant difference in the influence between depth jump and jump to box training methods on smash ability with sig values (0.04)< α (0.05) and Fcalculate values (7.027) > Ftable (4.49), (2) There is a difference in the influence of height above average and height below average on smash ability where the significance value is (0.030), < α (0.05) and Fcalculate (5.317) > Ftable (4.49), (3) There is an interaction between plyometrics training methods and height on smash ability with sig (0.027) < α (0.05) and Fcalculate (8.603) values > Ftable (4.49). Conclusions from this study: (1) There is a significant difference in influence between depth jump and jump to box training methods on volleyball smash ability, 2) There is a significant difference in influence between height above average and height below average on volleyball smash ability, 3) There is an interaction between pliometric training methods and height on volleyball smash ability.